Case Report: Right atrial mass arising from the Eustachian valve - Jolou, Jalal; Martineau, Jérôme; Müller, Hajo; Cikirikcioglu, Mustafa; Huber, Christoph (Frontiers in Cardiovascular Medicine, 2023)
A mass in the right atrium (RA) is an unusual finding that warrants further investigation. We report the case of a 72-year-old male patient who underwent a Bentall operation with a biological composite graft and closure of patent foramen ovale 18 months prior to his presentation with an incidental new RA mass during follow-up echocardiography. A transesophageal echocardiography and thoracic CT angiography confirmed a right atrial mass attached to the Eustachian-valve and additionally revealed a non-occlusive pulmonary embolism in the inferior lobar artery of the left lung.